A Framework for Developing Green Coordinated Decision Model In Supply Chain - Achmad Chairdino Leuveano, Raden; Nizam Ab Rahman, Mohd; Md Deros, Baba; Mohd Faizal Wan Mahmood, Wan (International Journal of Engineering and Technology, 2019)
In the supply chain (SC), cost reduction always becomes the main aspect for the success of the competitive market. Minimizing costs in SC can be obtained through various methods. One of the methods is to coordinate decisions among members in SC. In the recent competitive, cost reduction is not only the main objective but also carbon emission reduction has become serious problems in SC. To achieve that, coordination in SC should cover both performances to achieve green SC. Therefore, this paper proposes a framework for developing a green coordinated decision model (GCDM) under costs and carbon emissions consideration. The model considers the decision-making process for solving inventory replenishment problem in SC to solve the economic and environmental problem. The developed framework is based on reviewing the past literature on the SC decision model. There are four major steps of the proposed framework: 1) defining actors and operations involved in supply chain, 2) defining parameters, variables, and performance of the model, 3) defining the modeling process, and 4) verification and validation of the model. This framework contributes to the knowledge where the modeler can provide an insight in generating an accurate decision model and its solution to improve the environmental performance.Â Â Â